Characterization of aluminum films deposited on silicon substrate by radio frequency (RF) magnetron sputtering - Flauta, Randolph E. (1999)
A study made to determine the characteristics of aluminum thin films deposited on type (lll) silicon (Si) substrate using Radio Frequency (RF) magnetron Sputtering at different operating conditions. The parameters studied include the RF power, deposition time (DT) and operating pressure (OP). The RF power ranged from 75 to 200 Watts. The deposition time ranged from 5 minutes for thin deposits to 2 hours for thicker deposits at varying power and pressure. The operating pressure was set at 5 and 10 mTorr. The minimum ignition pressure was set at 30 mTorr and the base pressure ranged from 4.0 x 10-⁶ to 2.0 x 10-⁵ mTorr.
Surface morphology examinations were made using the Scanning Electron Microscope (SEM) and Atomic Force Microscope (AFM) to determine the film thickness, surface roughness, and average grain size of the sputtered samples. The thickness monitor inside the deposition chamber was calibrated for thickness determination. This was done by etching a step on the film with HF followed by examination of the etched and unetched part by AFM. The crystal structure of the deposited film was examined using the X-ray Diffractrometer. The Al film deposited exhibited preferred orientation with the (200) peak being the most dominant.
The thickness of the Al film was found to increase linearly with respect to deposition time and RF power. Increasing the operating pressure resulted to decrease in film thickness. The highest deposition rate achieved was 90A/minute at RF power of 200 W, deposition time of 2 hours and operating pressure of 5 mTorr. Using the deposition parameters mentioned, the film thickness attained is around 1µm. Thicker samples produced a rougher surface. Parametric study revealed significant two-factor and three-factor interactions among RF power, deposition time, and operating pressure.
The total resistance was measured using a two-point probe wafer parametric analyzed and the sheet resistance using the four-point probe setup. using the four-point probe, it was found out that the sheet resistance of the film decreased as the film thickness was increased. For the thicker films produced, the resistivity of the Al films approached that of the bulk resististivity.
Thesis (M.S. Materials Science & Engineering)--University of the Philippines, Diliman.
Keywords: Aluminum films; Sputtering (Physics).